Gene Expression in Rat Hearts Following Oral Administration of a Single Hepatotoxic Dose of Acetaminophen - Jin, Seon Mi (Yonsei University College of Medicine, 2012)
PURPOSE: Toxicity caused by acetaminophen and its toxic mechanisms in the liver have been widely studied, including effects involving metabolism and oxidative stress. However, its adverse effects on heart have not been sufficiently investigated. This study evaluated the cardiac influence and molecular events occurring within the myocardium in rats treated with a dose of acetaminophen large enough to induce conventional liver damage. MATERIALS AND METHODS: Male rats were orally administered a single dose of acetaminophen at 1,000 mg/kg-body weight, and subsequently examined for conventional toxicological parameters and for gene expression alterations to both the heart and liver 24 hours after administration. RESULTS: Following treatment, serum biochemical parameters including aspartate aminotransferase and alanine aminotransferase were elevated. Histopathological alterations of necrosis were observed in the liver, but not in the heart. However, alterations in gene expression were observed in both the liver and heart 24 hours after dosing. Transcriptional profiling revealed that acetaminophen changed the expression of genes implicated in oxidative stress, inflammatory processes, and apoptosis in the heart as well as in the liver. The numbers of up-regulated and down-regulated genes in the heart were 271 and 81, respectively, based on a two-fold criterion. CONCLUSION: The induced expression of genes implicated in oxidative stress and inflammatory processes in the myocardium reflects molecular levels of injury caused by acetaminophen (APAP), which could not be identified by conventional histopathology.